Effectiveness of Breastfeeding Techniques to Improve Latching and Prevention of Nipple Soreness among Primipara Mothers. A Randomized Control Trial - Taj, Shazia; Kausar, Prof. Dr. Samina; Naz, Farah; Manzoor, Nadia; Zareef, Sana (Journal of Neonatal Surgery, 2025)
Background Breastfeeding is crucial for reducing child mortality but challenges like nipple soreness and improper latching techniques can lead to early cessation. Breastfeeding status assessment rely on subjective, Not assessd objectively. Methodology A study of 100 postpartum primipara mothers used an experimental design with non-probability convenient sampling. Participants were divided into two groups:SVD and Pfannenstiel incision, each split into intervention and control subgroups by randomization. The intervention group received breastfeeding supportive techniques, while the control group received routine care. Data was gathered by socio-demographic form, the LATCH scoring system, and a nipple soreness scale by using SPSS version 3023. Data Analysis was conducted by using descriptive statistics, t-tests and ANOVA to evaluate the effectiveness of techniques. Results The study results revealed significant reductions in nipple soreness among intervention group mothers as Latch observations of intervention group was (8.84 ± 1.22). Nipple soreness score of intervention group was (0.44 ± 0.85) & control (2.12 ± 1.20) accordingly. Conclusion Proper positioning and latch are crucial for minimizing nipple soreness and newborns can efficiently draw milk from the breast. Therefore, it is crucial for nurses to objectively assess breastfeeding by implementing a LATCH charting system.